Существование и единственность решения задачи Коши для сингулярных систем ингегро-дифференциальных уравнений - Шмарда, З. (Український математичний журнал, 1993)
Sufficient conditions are established for the existence of a unique solution of the Cauchy problem for singular systems of integro-differential equations.